EFEKTVITAS PEMBELAJARAN STATISTIK BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Lilik Mustofiyah; Nina Mekalungi; Zunan Azis; Budi Murtiyasa; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the effectveness of problem-based statistical learning models in enhancing elementary school students' understanding of concepts and problem-solving skills. The population in this study consists of all sixth-grade students at SDN Banjarejo in Madiun City, comprising two classes, each with 28 students. Using a quasi-experimental non-equValent control group design, two classes were identified as experimental and control groups. The experimental class implemented problem-based learning, while the control group followed conventional learning methods. Data were collected through pretests and posttests and analyzed using independent t-tests and paired t-tests. The results show that problem-based learning significantly improves concept understanding and problem-solving abilities compared to conventional methods. The experimental group recorded an average increase of 23 points in posttest scores, while the control group increased by only 10 points. Statistical analysis indicates a significant difference between the two groups in posttest score improvement (t-value = -3.45, df = 54, p < 0.05). These findings affirm that problem-based statistical learning approaches are effectVe in enhancing students' mathematics learning outcomes, providing relevant learning contexts and increasing student engagement in the learning process. The implications of this research support the use of innovatVe learning models to strengthen mathematical concept understanding at the elementary school level.